CONSUMER RESPONSES TO THE USE OF VISUAL RHETORIC IN ADVERTISEMENT CASE STUDY: CITRA PARIWARA PARTICIPANTS ADVERTISEMENT - Himawan Mulyadi, Riki
One of the ways commonly used to increase the appeal of an advertisement is to use visual rhetoric rules. Visual rhetoric is a symbolic language that is expressed visually. The use of visual rhetoric will produce visual advertisements that are entertaining and not easily forgotten by the audience. Advertisement for the antiseptic drug Vidisep, advertisement for Super Zuper candy, and advertisement for muscle pain medication Neo Rheumacyl are advertisements that use a visual rhetoric approach in their attempts to communicate. These three advertisements are participants in the annual Indonesian advertising contest, Citra Pariwara. This indicates that as a visual work, these three advertisements meet the requirements in terms of creativity in their visualization. However, it is not yet known how the correlations between creatively made advertisements and the response from consumers. This research aims to see consumer responses to advertisements that use visual rhetoric approach in a depth. In this research, Vidisep, Super Zuper, and Neo Rheumacyl advertisements are the object of the case study. The status of the three advertisements as participants of Citra Pariwara is one of the reasons for their selection as the object of research. Another reason is the three advertisements have made achievements in these activities. It is interesting to know the response of consumers to the three print media advertisements that have performed well in the Citra Pariwara competition. The method used in this research is a qualitative method. Data collection was carried out through in-depth interviews. The goal is to find out a deep understanding of consumer responses to advertisements that use a visual rhetoric approach. The study used two stages of research. In the early stages, research was carried out aimed at identifying the presence and types of visual rhetoric in advertisements. The second stage of research is the main research that deals with knowing and understanding consumer responses. 4 The analysis carried out for the first stage is to use model of the Taxonomy of Rhetorical Figures in Advertising Its function is to explain the types of rhetoric contained in advertisements and to understand the rhetorical operations that are taking place. Whereas for the second stage, the analysis uses the Cognitive Response Approach model. This model is a way to see consumer responses to an advertisement with an emphasis on cognitive aspects. Meanwhile, Model Of The Cognitive And Emotional Processing Of Rhetorical Works is used to explain the relationship that occurs in the second stage with the visual rhetoric contained in the advertisement. The results of the analysis in the first stage of research showed that the three advertisements met all the requirements as advertisements using a visual rhetoric approach. Each is identified as having a different type of visual rhetoric. The three advertisements use a trope-type rhetorical figurative mode. Advertising that uses tropes in conveying its message requires audiences who are able to understand implicit meanings. Meanwhile, the results of the second stage of research show that consumer responses are related to brand attitudes which play a greater role in generating trust. Consumers trust advertising claims because they are familiar with the brand and are supported by the good name of the manufacturer. Attitude toward the advertisement can only provide entertainment. Creative and entertaining advertising visualization does not necessarily mean that consumers will interpret the message. The success of interpreting advertising visualization using a visual rhetoric approach depends on the accuracy in choosing the visual form. The results of the research are expected to be able to provide input regarding consumer responses in Indonesia to advertisements that prioritize creativity in their visualization. Research on the use of visual rhetoric in this case is also expected to increase understanding the importance of the success of visual meaning process. Another hope is that this research can be the start of further research on the relationship between the use of visual rhetoric in advertising and consumer responses.